Maximum Power Extraction Method for a Doubly-fed Induction Generator Wind Turbine - Dinh Chung Phan; Trung Hieu Trinh (Institute of Advanced Engineering and Science, 2018)
This research presents a new scheme to extract the maximal available power from a wind turbine employing a doubly fed induction generator (DFIG). This scheme is developed from the wind turbine’s MPPT-curve. Furthermore, we propose control laws for the rotor and grid side-converters. The stability of the proposed maximum available power method and the control laws are proved mathematically upon Lyapunov’s stability criterion. Their efficiency is tested through the simulations of a DFIG wind turbine in Matlab/Simulink. Simulation results are analyzed and compared with that using a conventional scheme. Thanks to the suggested scheme, the wind turbine can track its maximum power point better and the electric energy output is higher comparing with that using the conventional scheme. Furthermore, by the suggested controllers, the rotor speed and current of the DFIG converged to their desired values. In other words, the wind turbine can achieve stable operations by the suggested control laws.